EFFECTIVENESS OF THE QODU METHOD IN ENHANCING TUBERCULOSIS PROGRAM PLANNING AT PRIMARY HEALTH CENTERS - Herin Mawarti; Binti Sukartini; Achmad Zakaria (Universitas Aisyah Pringsewu, 2026)
The success of tuberculosis (TB) control is strongly determined by effective program planning at the primary healthcare level. The 2020–2024 National TB Control Strategy applies a People-Centered Framework (PCF), however, planning methods such as USG, FGD, CARL, and SWOT are often considered complex. This study evaluated the Quadrant of Difficulty–Usefulness (QoDU) method as a simpler and more practical alternative for prioritizing TB programs. A quasi-experimental quantitative design with a pre–post test approach was applied to 34 TB program officers at primary health centers in Jombang Regency, with data analyzed using the Wilcoxon Signed Rank Test.Findings indicated significant improvements across nearly all QoDU variables (p0.005). Median scores for reliability rose from 6 to 8, response time from 6 to 7, usability from 6 to 8, and ease of understanding from 6 to 8. Other aspects such as completeness, relevance, personalization, and security also improved significantly (p=0.000–0.002). Service elements, including assurance, empathy, and responsiveness, showed notable progress. From the user perspective, satisfaction, willingness to reuse, and overall experience increased. Efficiency gains included cost savings, wider coverage, and time efficiency.In conclusion, QoDU proved easier, faster, more efficient, and generated better-quality data than conventional methods. It shows strong potential for broader application in health programs and, with digitalization, may enhance planning effectiveness and accelerate TB elimination efforts.